2016
DOI: 10.4049/jimmunol.1502543
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Longitudinal Study of HIV-1 Env Vaccine–Elicited B Cell Responses to the Virus Primary Receptor Binding Site Reveals Affinity Maturation and Clonal Persistence

Abstract: Due to the genetic variability of the HIV-1 envelope glycoproteins (Env), the elicitation of neutralizing antibodies to conserved neutralization determinants including the primary receptor binding site, CD4 binding site (CD4bs), is a major focus of vaccine development. To gain insight into the evolution of Env-elicited antibody responses, we utilized single B cell analysis to interrogate the memory B cell Ig repertoires from two rhesus macaques following five serial immunizations with Env/adjuvant. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…JR-FL-reactive Env ϩ memory B cells accounted for approximately 0.15% of IgG ϩ B cells (Fig. 1B), which was lower than the Env ϩ memory B cell frequency (ϳ5%) sorted by the autologous antigen, YU2gp140-F, reported previously (15). This suggested that JR-FL SOSIP.664 was a more selective probe than the probes deployed previously.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…JR-FL-reactive Env ϩ memory B cells accounted for approximately 0.15% of IgG ϩ B cells (Fig. 1B), which was lower than the Env ϩ memory B cell frequency (ϳ5%) sorted by the autologous antigen, YU2gp140-F, reported previously (15). This suggested that JR-FL SOSIP.664 was a more selective probe than the probes deployed previously.…”
Section: Resultsmentioning
confidence: 63%
“…1A, lower panel). To define the cross-reactive tier 2 virus neutralizing B cell response in macaque K17, we sorted antigen-specific memory B cells by fluorescence-activated cell sorting (FACS) and applied Ig cloning methods optimized for NHP B cell repertoire analysis (10,15). We employed a heterologous Env trimer, JR-FL SOSIP.664, a native clade B Env spike mimetic derived from primary isolate JR-FL (25), as the sorting probe.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations